Voices of Change: Bangladeshi ESL Teachers' Perspectives on Pedagogical Innovations - Yeasmin, Farida; Younus, Md Abdullah Al (International Journal of Language and Literary Studies, 2025)
This qualitative study determines how Bangladeshi ESL teachers perceive the impact of recent pedagogic innovations on their teaching, the challenges they face in implementing them, and how they foresee ESL education in the future. The research adopts a phenomenological study design to develop an understanding of the lived experience and perception of 15 ESL teachers from diverse educational institutions across Bangladesh. Purposive sampling guarantees the identification of research participants with first-hand experience in pedagogical innovations. Data collection is characterized by in-depth, semi-structured interviews administered in Bengali to collect nuanced responses. Thematic analysis produces critical findings: teachers acknowledge the potential of interactive approaches and digital technology in augmenting learners' engagement; however, they are confronted by insurmountable obstacles, including inadequate access to technology and the drawbacks of large classes. Teachers envision a future situation where ongoing professional development and infrastructural assistance are the key elements for the effective application of new pedagogical methods. The results stress the necessity for customized professional development modules, better infrastructure, and policy reform to develop an environment conducive to innovation for ESL education. This study contributes to the body of knowledge about effective ESL instruction in resource-poor environments. It has practical implications for educators, policymakers, and stakeholders interested in improving ESL education in Bangladesh.